Impact of transcatheter mitral valve repair using MitraClip on right ventricular remodeling - Ledwoch, Jakob; Fellner, Carmen; Hoppmann, Petra; Thalmann, Ruth; Kossmann, Hans; Dommasch, Michael; Dirschinger, Ralf; Stundl, Anja; Laugwitz, Karl-Ludwig; Kupatt, Christian (International Journal of Cardiovascular Imaging, 2020)
The potential of the MitraClip to prevent from right heart failure or to restore right ventricular (RV) function is still unclear. The aim of the present study was to analyze the impact of the MitraClip implantation on RV function and its association with clinical outcome. After MitraClip implantation patients underwent echocardiography follow-up scheduled between 3 and 6 months after the procedure in the present single-center registry. A total of 93 patients were included. Compared to baseline, RV function declined in 20%, was unchanged in 25% and improved in 55% of the patients. Factors associated with decline in RV performance were atrial fibrillation, decrease in left ventricular function and lack of reduction in pulmonary artery pressure. Patients who experienced worsening in RV function had a significantly lower survival after mean follow-up of 11 ± 7 months compared to those with preserved or improved RV function (15% vs. 83% vs. 83%; p log rank = 0.001). Furthermore, changes in TAPSE were found to be an independent predictor for all-cause mortality [HR 0.88 (0.77–0.99); p = 0.04]. The majority of patients suffering from severe MR benefited from MitraClip with respect to RV remodeling. However, 20% of the patients experienced a decline in RV function, which was associated with poor prognosis. Importantly, changes in RV function after MitraClip were identified as independent predictor for survival in contrast to baseline RV function and, therefore, should be implemented in follow-up routine for better outcome prediction.
CRIS-Team Scopus Importer:2023-03-08
Keywords: MitraClip; Mitral regurgitation; Pulmonary hypertension; Remodeling; Right ventricular function